The social pandemic from SARS-CoV-2 among Italian university students: a pilot study - Russo, Claudio; Giordano, Giuseppe; Marsico, Giuseppina (Psychology Hub, 2022)
The impact of restrictions on movement resulting from the SARS-CoV-2 pandemic may contribute to a disruption of mental health in young people during this era. In March 2021, lockdown restrictions were enforcing national policies of tackling the infectious disease across the globe. In the early stages of the vaccination rollout, public enquires on confidence to endure the virus pandemic have shown high levels of psychological distress. Under the above circumstances, 333 university students were asked to fill in an online-based survey on alcohol consumption, compulsive behavior as a loss of control over eating, fear of weight changes, excessive sleepiness and sleep deprivation. Text mining and multiple correspondence analysis were employed to analyze qualitative data on the lived experience against the occurrence of health-related behaviors. Data analyses have showed that the pandemic was associated with a mixed breakup of clustered lemmas based on sex, age, and relationship status. The extent to which the participants have reported a lower degree of satisfaction on living arrangements, intimate and family relationships were interpreted as meaningfully related with a more negative lived experience. Social confinement has resulted as an immediate action for mitigating a public health crisis from the SARS-CoV-2 disease. Incidentally, social measures to mitigate the virus transmission have sought to protect internal collapse of the health care systems by reducing the number of casualties. Conversely, these findings provide new evidence on the social determinants of health among youth and consequently highlight the potential interference from missing social interactions in the COVID-19 pandemic response